PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF SISWA - Putri, Defia Laili Mustafik; Susilowati, Susilowati; Berprihatin, Berprihatin; Salsabila, Atika; Kurniasari, Desi; Oktaviantry, Dinar Ajeng; Apriliani , Dwi; Tryas, Sumadaning (Steam Engineering, 2025)
This study aims to analyze the application of the Problem Based Learning in improving students' cognitive abilities in Danish Pastry material. The type of research used is classroom action with Kemmis & McTaggart model design which includes two cycles. Each cycle includes the stages of planning, implementation, observation, reflection. The population of the study was 32 culinary class XI students. The sampling technique used purposive sampling. The data analysis technique used a cognitive test result completion test, analysis of teacher and student activities through observation sheets, and the N-gain test. The results showed that application of PBL significantly increased the activities of teachers and students. With the percentage of teacher activity increasing from (95.29%) to (97.17%) while student activity increased from (85.63%) to (88.12%). Cognitive learning outcomes increased from pre-test (15.63%) to post-test (62.50%) in cycle I and increased further to reach completion reaching (100%) in cycle II. The results of N-Gain analysis showed a significant increase from the medium category (0.339) to the high category (0.942). The conclusion of this study is that application of PBL is effective in improving students' cognitive understanding, allowing students to be more active in problem solving, critical thinking, and understanding concepts in depth